Seasonal changes in neuronal turnover in a forebrain nucleus in adult songbirds. Issue 4 (14th November 2018) - Larson, Tracy A.; Thatra, Nivretta M.; Hou, Darren; Hu, Rachael A.; Brenowitz, Eliot A.
Abstract: Neuronal death and replacement, or neuronal turnover, in the adult brain are one of many fundamental processes of neural plasticity. The adult avian song control circuit provides an excellent model for exploring mature neuronal death and replacement by new neurons. In the song control nucleus, HVC of adult male Gambel's white‐crowned sparrows ( Zonotrichia leucophrys gambelli ) nearly 68, 000 neurons are added each breeding season and die during the subsequent nonbreeding season. To accommodate large seasonal differences in HVC neuron number, the balance between neuronal addition and death in HVC must differ between seasons. To determine whether maintenance of new HVC neurons changes within and between breeding and nonbreeding conditions, we pulse‐labeled two different cohorts of new HVC neurons under both conditions and quantified their maintenance. We show that the maintenance of new HVC neurons, as well as new nonneuronal cells, was higher at the onset of breeding conditions than at the onset of nonbreeding conditions. Once a steady‐state HVC volume and neuronal number were attained in either breeding or nonbreeding conditions, neuronal and nonneuronal maintenance were similarly low. We found that new neuronal number correlated with a new nonneuronal number within each cohort of new neurons. Together, these data suggest that sex steroids promote the survival of an initial population of new neurons and nonneuronal cells entering HVC. However, once HVC is fully grown or regressed, neuronal and nonneuronal cell turnover is regulated by a common mechanism likely independent of direct sex steroid signaling. Abstract : Sex steroids promote the maintenance of an early cohort of new neurons within the avian sensorimotor nucleus HVC. This addition of new HVC neurons at the onset of breeding season contributes to the growth of HVC and an increase in singing behavior. Once HVC volume and neuron number is stable, neuronal turnover, or the balance between neuronal birth and death, returns to homeostasis. These results confirm that both new and older neurons die as HVC grows and regresses across seasons.